PANoptosis in Cancer: Molecular Mechanism, Current Evidence, and Therapeutic Implications - Yuqing Peng; Huifang Zhao; Chenxin Yang; Xiangling Wang; Shuai Zhang (Journal of Bio-X Research)
PANoptosis has been shown to play important pathophysiological roles, particularly in cancer. This review summarizes the composition and functions of PANoptosis and its associated PANoptosomes, including the ZBP1, RIPK1, AIM2, and NLRP12-PANoptosomes. Predictive models based on PANoptosis markers have been developed to guide personalized treatment strategies, highlighting novel therapeutic targets. Research into compounds that modulate PANoptosis pathways is ongoing, with the aim of increasing cancer treatment efficacy and addressing challenges such as drug resistance and immune evasion. This review also summarizes innovative PANoptosis-related prognostic gene signature models and compounds that modulate PANoptosis pathways.